Prediction of Pd/C Catalyst Deactivation Rate and Assessment of Optimal Operating Conditions of Industrial Hydropurification Process - Azarpour, A. (American Chemical Society, 2015)
One of the key concerns of the purification section of a purified terephthalic acid (PTA) production plant is the deactivation of palladium supported on carbon (Pd/C) catalyst. In this work, the deactivation rate model of 0.5 wt Pd/C catalyst has been developed considering temperature, active surface area, and residual catalytic activity. Moreover, the optimal operating conditions of the industrial hydropurification process have been investigated. The results show that PTA production rate (PPR) can be improved by 5.4 through 18 increase in hydrogen flow rate. Furthermore, PPR can be increased by 7.6 via the temperature rise in the reaction mixture. The optimization results further reveal that PPR can be enhanced by 17.3 by improving the feed concentration under the normal operation by means of limiting the inlet 4-carboxybenzaldehyde concentration. The research findings can be applied in the actual working plant to enhance the efficiency of the hydropurification process. Â© 2015 American Chemical Society.